Hollow mesoporous silica supported PtIr bimetal catalysts for selective hydrogenation of phenol: significant promotion effect of iridium. Issue 50 (20th June 2017) - Zheng, Yuying; He, Peishan; Fang, Yanxiong; Yang, Xu; Liang, Huagen
Abstract : Ir promoted Pt catalyst is prepared using hollow mesoporous silica as support. It shows high hydrogenation rate of 4255 mmol h −1 gPt −1 at mild conditions (50 °C and 0.5 MPa of p H2 ). The promotion effect of Ir contributes to the enhanced activity. Abstract : Selective hydrogenation of phenol is of great significant for the production of Nylon 6. Herein, highly efficient and stable Ir promoted Pt catalysts for the hydrogenation of phenol are prepared by deposition of Pt–Ir nanoparticles onto hollow mesoporous silica spheres (HMSs) through a facile wet-impregnation and H2 reduction method. The obtained PtIr/HMS catalyst with Ir/Pt molar ratio of 0.1 shows a highest hydrogenation rate of 4255 mmol h −1 gPt −1 with cyclohexanone selectivity of 85% at 50 °C and 0.5 MPa of p H2, which is 3 times and 8.6 times higher than that of the mono Pt/HMS catalyst and commercial Pt catalyst, respectively. The trace addition of Ir promoter essentially contributes to the enhanced hydrogenation activity by improving the metal dispersion of Pt nanoparticles and promoting the charge transfer between the Pt and Ir. This work provides an effective protocol in developing high performance catalysts for phenol hydrogenation under mild reaction conditions.